Diagnosis and management of pancreatic insufficiency in patients with gastrectomy due to cancer or gastric ulcers: a virtual roundtable expert discussion - Croagh, Daniel; Michalski, Christoph; van Berge Henegouwen, Mark I.; Alfieri, Sergio (Expert review of gastroenterology & hepatology, 2023)
Pancreatic exocrine insufficiency (PEI) is common after gastric resection for cancer or ulcers but is under-recognized and undertreated. Although pancreatic enzyme replacement therapy (PERT) is the mainstay of PEI management, robust evidence supporting its use after gastric surgery is limited. In the absence of guideline recommendations specific for patients with pancreatic insufficiency after gastrectomy, a panel of experts from different geographical regions convened in a virtual meeting to discuss their approach to patient management. Pancreatic insufficiency after gastrointestinal surgery is not a simple post-surgical complication as several factors contribute to its development. Although the pancreas is unimpaired after gastrectomy, it cannot function normally in the altered environment. Pancreatic insufficiency can be challenging to diagnose in gastrectomy patients due to nonspecific symptoms and the absence of a simple diagnostic test. Fecal elastase appears to be the default test, although it is not sufficiently sensitive nor reliable for diagnosing or monitoring PEI. Patients with maldigestion symptoms after gastrectomy are treated pragmatically: those with clinical suspicion of pancreatic insufficiency receive a trial of PERT and are monitored for symptom improvement. There is a clear need for high-quality evidence from clinical trials to guide the management of this patient population.
Gesehen am 15.03.2024